The future of securities regulation - Luigi Zingales (Fondazione Eni Enrico Mattei (FEEM), 2009)
The U.S. system of security law was designed more than 70 years ago to regain investors' trust after a major financial crisis. Today we face a similar problem. But while in the 1930s the prevailing perception was that investors had been defrauded by offerings of dubious quality securities, in the new millennium, investors' perception is that they have been defrauded by managers who are not accountable to anyone. For this reason, I propose a series of reforms that center around corporate governance, while shifting the focus from the protection of unsophisticated investors in the purchasing of new securities issues to the investment in mutual funds, pension funds, and other forms of asset management.
Keywords: G2; G28; G01; 330; US Security Law; Securities Regulation; Trust